Labour market as determinant of functioning of local production systems – the case of Lodzkie Region and Novosibirsk Oblast - Arendt, Lukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The development of local production systems depends on many interlinked factors – localisation, available infrastructure, the abundance of natural resources, stock of human capital, etc. Undoubtedly, human resources play a crucial role in the creation and development of LPS, especially in cases, where competitive advantage of a LPS is knowledge-intensive based. The paper presents the changes on the labour market in two regions: Lodzkie Region and Novosibirsk Oblast in order to discuss the way, in which human capital and labour market situation may determine the development of local production systems in these regions. Research results show, that it is fundamental both to invest in human capital and to develop educational and research potential in accordance with labour market needs in order to reduce detrimental impact of society ageing in these regions.